Dynamic Response Analysis of Jacket Platform Integrated With Oscillating Water Column Device - Qiao, Dongsheng; Feng, Changlong; Ning, Dezhi; Wang, Chang; Liang, Haizhi; Li, Binbin (Frontiers in Energy Research, 2020)
For the marginal oilfield with low oil extraction, adding wave energy conversion device integration to the jacket platform is very meaningful for reducing the mining cost. First, the design concept of integrated oscillating water column (OWC) device with jacket platform is proposed. Then, the optimal model of OWC device structural arrangement parameters is established with the aim of low wave force and high wave energy conversion efficiency. Finally, the dynamic response of the integrated device is analyzed under the working and extreme sea states. The results show that the integrated device has certain effectiveness and feasibility.